Improved external device for a mass-carrying sliding system for shaking table testing. - Carrillo, Julian (Earthquake engineering & structural dynamics.)
Shaking tables are suitable facilities to assess and validate the behavior of structures and nonstructural components under actual seismic actions. Because of the size and weight limitations of the tables, some approaches, like testing reduced-scale models or testing only the main structural components, are deemed necessary. In these cases, to comply with modeling requirements, large amount of extra-mass should be added to the specimen. Therefore, to avoid the risk of lateral instability of models, to maintain the weight of test specimens within table payload, while maintaining the amount of mass needed, an external device for transmitting the inertia forces to the models using an improved sliding system is proposed. Although friction devices for similar purposes have been developed using sliding bearings (Teflon pads or rollers), the measured coefficient of dynamic friction and the energy dissipated by friction have been very high. In order to drastically diminish the damping added to the specimen response when a friction device is used, the improved device employs a linear motion guide system (LMGS) with very low friction. Shaking table tests to collapse of reinforced concrete walls were used to evaluate the effectiveness of the proposed device. Measured dynamic friction coefficients, spectral accelerations and hysteresis loops show that friction developed in the LMGS did not add any significant amount of damping into the specimen response. Thus, the proposed device is a reliable and suitable mass-carrying sliding system (MCSS) for dynamic testing using medium-size shaking tables.